Health Information Crisis during COVID‐19 in the South Asian Region: Challenges, Experiences, Resilience, and Collaborative Efforts. Issue 1 (14th October 2022) - Gala, Bhakti; Chu, Sam; Islam, Md. Anwarul; Hina Batool, Syeda; Chan, Helen; Kumar Bhardwaj, Raj; Lamba, Manika; Kanchana Jayasekara, Prasadi
Abstract: The fight against the COVID‐19 pandemic is as much an information war as it is a medical war. Members from South Asia and the Asia Pacific countries share their experiences and challenges faced with collaborative responses for the ASIS&T Special Chapter funded project on "Dealing with COVID‐19 and saving people's lives in South Asia (SA) areas & beyond—A Health Informatics Promotion Project" awarded to the South Asia Chapter in 2021. The panel discusses the challenges faced within the context of geopolitical, socio‐economic, religious, and cultural conditions prevalent within their countries. In the first 40 minutes, panel members narrate their own experiences by sharing their personal stories about this collaborative project and share the challenges of content creation and promotion from within the context of their respective countries. The next 30 minutes will be facilitated by the panel chair inviting a discussion between panel members and the audience to engage and come up with innovative ideas, discuss challenges in creating multilingual content and suggestions for improving the project outcome as well as shed light on initiating future health informatics project in similar regions. The last 20 minutes will culminate with the summarization of these collaborative experiences.